2007
DOI: 10.1359/jbmr.070106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Determinants of Volumetric and Areal BMD in Multi-Generational Families of African Ancestry: The Tobago Family Health Study

Abstract: BMD is higher and fracture risk is lower among individuals of African versus European descent, but little is known about the genetic architecture of BMD in the former group. Heritabilities of areal and volumetric BMD were moderate in our large families of African descent but differed for trabecular and cortical BMD.Introduction: Populations of African ancestry have lower osteoporotic fracture risk and higher BMD than other ethnic groups. However, there is a paucity of information regarding the genetic and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Numerous family and sibling studies of peak BMD have been performed in a variety of populations, and these studies have universally shown the high heritability of peak BMD [3,8,21,29,30]. Many whole genome linkage scans have also been performed, with QTLs reported at a number of chromosomal regions, though specific QTLs have rarely been replicated across studies [5][6][7]28,[31][32][33][34][35][36], probably due, in part, to genetic heterogeneity among the populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous family and sibling studies of peak BMD have been performed in a variety of populations, and these studies have universally shown the high heritability of peak BMD [3,8,21,29,30]. Many whole genome linkage scans have also been performed, with QTLs reported at a number of chromosomal regions, though specific QTLs have rarely been replicated across studies [5][6][7]28,[31][32][33][34][35][36], probably due, in part, to genetic heterogeneity among the populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…This high BMD potential may not be realized among native Africans due to nutritional and lifestyle factors [12]. It is reasonable to consider that the lower levels of genetic European and East Indian admixture among Tobagonian women, in the context of better nutrition and lifestyle factors, may be a possible reason for the higher BMD that we observed in this analysis compared to American Blacks, where European admixture is more prevalent [7,21,27,28].…”
Section: Discussionmentioning
confidence: 67%
“…Reference data did not allow for direct comparison of volumetric BMD [4], which takes bone depth into consideration, between Tobagonian and U.S. women. Research suggests that people of African ancestry may have genetic potential for higher BMD compared to people of European ancestry [7,27]. This high BMD potential may not be realized among native Africans due to nutritional and lifestyle factors [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because bone mineralization results from a complex interaction of genetic programming [27] and environmental and lifestyle factors [28,29], primary endpoints of BONEII include pharmacogenetic and bone metabolic biomarkers, lifestyle assessment, nutritional intake, and medical history.…”
Section: Selected Measuresmentioning
confidence: 99%